Analisis Yuridis Akta Perdamaian (Van Dading) sebagai Penyelesaian Sengketa Waris terhadap Anak Menurut Hukum Islam: Studi Putusan Akta Perdamaian Nomor 98/PDT.G/2024/PA.WGW - Dwina Avrilla; hasim purba; Rosnidar Sembiring (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Islamic inheritance disputes often arise due to conflicting interests and ambiguity in the distribution of estate assets. A deed of settlement (van dading) serves as one legally recognized and binding dispute resolution mechanism, even carrying executorial force when ratified by a court. However, problems emerge when the deed of settlement fails to specify the distribution of inheritance rights clearly, particularly with respect to minor children. This normative legal research examines the legal standing, binding force and juridical analysis of deeds of settlement in Islamic inheritance disputes, concluding that precision in drafting such deeds is crucial to ensure legal certainty, justice and the protection of all heirs' rights.